Fiscal consolidation in the euro area: long-run benefits and short-run costs. - Günter Coenen; Matthias Mohr; Roland Straub (European Central Bank (ECB), 2008)
In this paper, we examine the macroeconomic effects of alternative fiscal consolidation policies in the New Area-Wide Model (NAWM), a two-country open-economy model of the euro area developed at the European Central Bank (cf. Coenen et al., 2007). We model fiscal consolidation as a permanent reduction in the targeted government debt-to-output ratio and analyse both expenditure and revenue-based policies that are implemented by means of simple fiscal feedback rules. We find that fiscal consolidation has positive long-run effects on key macroeconomic aggregates such as output and consumption, notably when the resulting improvement in the budgetary position is used to lower distortionary taxes. At the same time, fiscal consolidation gives rise to noticeable short-run adjustment costs in contrast to what the literature on expansionary fiscal consolidations suggests. Moreover, depending on the fiscal instrument used, fiscal consolidation may have pronounced distributional effects.
Keywords: E32; E62; 330; euro area; fiscal consolidation; Fiscal Policy; Keywords: DSGE modelling; limited asset-market participation; Haushaltskonsolidierung; Finanzpolitik; Eurozone; Theorie; EU-Staaten